Studi Analisis Pemikiran Muhammad Abduh tentang Modernitas Beragama dan Pembaharuan Pendidikan Islam - Zahra Mevia Aimerly; Asri; Marwah Novi Dwiyanti; Mayrani Putri Altaf; Suci Nur Awalin; Fahri Hidayat (Universitas Veteran Bangun Nusantara, 2025)
This research seeks to examine Muhammad Abduh’s perspectives on religiousmodernity and the renewal of Islamic education as an effort to overcome theintellectual and social stagnation faced by Muslims from the 19th century up tothe present time. The study adopts a qualitative descriptive method using alibrary research approach, drawing on primary references from Abduh’s ownwritings such as Risalah al-Tauhid and Tafsir al-Manar, alongside secondarysources from scholarly books and academic journals. The results indicate thatAbduh prioritized the role of rational thinking, the revitalization of ijtihad, theharmonization of religious sciences with modern knowledge, and the structuralreform of educational institutions. For Abduh, modernity does not involvecopying Western civilization blindly, but rather harmonizing Islamic teachingswith contemporary realities through reasoned and contextual interpretation. Hisreformist ideas continue to hold strong relevance today, especially in curriculumdevelopment, pedagogical innovation, educational governance, and thecultivation of learners’ moral character in the era of globalization. Consequently,Abduh’s intellectual legacy serves as a pivotal framework for shaping an Islamiceducation model that is dynamic, balanced, and forward-looking.